The Influence of Promotion Through Instagram Social Media on the Decision to Stay at Villa Air Manis Hill Residence - Juli Andra; Youmil Abrian (Pt. Threeple Herphi Educate, 2024)
This research began with the discovery of the occupancy rate of Villa Air Manis Hill Residence rooms that did not reach the target. This study aims to determine the influence of Instagram social media on the decision to stay at Villa Air Manis Hill Residence. This type of research is quantitative research with a causal associative method. The population in this study were guests staying at Villa Air Manis Hills Residence with a sample of 130 people. The data collection technique used was to distribute questionnaires. The instrument test used validity and reliability tests. Data processing and analysis used were data tabulation and data description. The analysis requirements test used normality tests, homogeneity tests and linearity tests. The research hypothesis testing used simple regression analysis. The results of this study are 1) Villa Air Manis Hill Residence social media promotion shows a sufficient category with a percentage of 63.2%, 2) The decision to stay at Villa Air Manis Hill Residence shows a sufficient category with a percentage of 67.6%, 3) The influence of social media promotion variables on the decision to stay is 15.2% with a significance value of 0.00 <0.05 thus X has an effect on Y.